Mapeamento dos inselbergs em Quixadá e Quixeramobim, Ceará: padrões morfológicos e distribuição. - Gomes, Eliomara Leite Meira (2023)
Inselberg fields are found on several continents, including South America, North America and Africa. In Brazil, one of the largest assemblages of these reliefs is the Quixadá-Quixeramobim granitic inselberg field, which consists of 195 inselbergs organised in two clusters corresponding to the Quixadá and Quixeramobim plutons. Despite the importance of these forms, their spatial distribution and morphological patterns are still little studied, especially based on morphometric parameters. The aim of this study was to analyse the distribution of inselbergs in relation to morphological and morphometric patterns. Radar and optical images with different spatial resolutions were used for the morphometric analysis of the inselbergs. Their boundaries were manually vectorised using GIS programs and their minimum and maximum heights were automatically extracted using an analysis and measurement tool inserted in the QGIS 3.28.4 Firenze software. Six core areas were identified with a high density of inselbergs, reaching 1.5 inselbergs per square kilometre. The distribution patterns are generally related to the geological characteristics of the plutons and their structural configuration.